Happy Geoscience Edu: A new geoscience education system in the time of COVID-19 - Choi, Yoon Jung; Lee, Sujeong; Lee, Eunsu; Park, Chanung; Park, Samgyu (Thai Geoscience Journal, 2022)
The COVID-19 pandemic weakened many education systems worldwide. As a geoscience education center, the International School for Geoscience Resources (IS-Geo) of the Korea Institute of Geoscience and Mineral Resources (KIGAM) also faced difficulties in educating the public during the pandemic. To overcome the difficulties of a face-to-face education system, IS[1]Geo created a new education system brand named “Happy Geoscience Edu”, which contains various home-training kits, special online courses, and small-group field training courses. Happy Geoscience Edu consists of four different courses: Happy Geoscience Box, Happy Geoscience Class, Happy Geoscience Talk, and Happy Geoscience Trip. In the ‘Happy Geoscience Box’ course, IS-Geo sends geoscience boxes to families with children. The box contains various geoscience experiment kits together with written instructions and scientific explanations. With this Happy Geoscience Box, parents can guide their children to run the experiments at home. ‘Happy Geoscience Class’ is an online education course mainly for primary to high school students. In classrooms, the students can learn geoscience experiment on a chosen topic through online lectures and follow the instructions. ‘Happy Geoscience Talk’ is an interactive event between KIGAM and the general public. Anyone can send their questions, within the suggested topic, to IS-Geo and then the experts from KIGAM will answer (talk) their questions via YouTube. All ‘talks’ are opened to the public since it aims to increase the public’s attention to geoscience. ‘Happy Geoscience Trip’ is a small-group field training course on UNESCO Geoparks in Korea. It aims to educate local commentators and the public about the detailed geology of the Geoparks. Happy Geoscience Edu has already received positive feedbacks in Korea. We hope this can inspire the education systems in other CCOP member countries.